Introductions and Their Significance in the Sentence. Different Aspects of Artwork Analysis from Separate Pieces (The Peerian Journal, 2022)
In the article, the artistic features of introductions and their importance in the sentence are discussed in detail. An attempt was made to provide information aimed at understanding the original content of the entries.